BT, a vital reshuffle in a stagnant industry - Amado, Guilherme Café Estêvão Pontes (2021)
This equity research analysis of the UK's telecommunications incumbent British Telecom aims to understand its business model and key implications. Such research starts by stressing out the pay out policy to properly advise the investor, later arriving at the operating segments where the company's incoming change on fiber rollout and spectrum acquisition will essentially be felt. After studying the competitors according to the economic framework, one can adequately address the revenue breakdown for the aforementioned divisions. Once BT enjoys a decent tax deal in the short term, it is crucial to understand the cost of capital. After getting acquainted with the core creation drivers, one suggests a recommendation based on a Discounted Cash Flow analysis. The recommendation is strengthened with comparables and sensitivity analysis.